Characteristics of sexual violence suffered by children seen by a support program - Kelly Linhares Vasconcelos; Adriana Gomes da Ferreira; Eliany Nazaré Oliveira; Danielle D’avilla Siqueira; Patrícia Neyva da Costa Pinheiro (Rev Rene)
In Brazil, statistics of sexual violence against children are far from showing the current reality in face of underreported cases. This study had the objective of characterizing sexual violence, suffered by children assisted by the Program Sentinela and the profi le of the aggressor in Sobral – Ceará from 2002 to 2006. The non intentional probabilistic sample was composed by 50 victims of sexual abuse and out of those, 66% are female, being the dominant age group of about 8 to 12 years old, (58%); in 36% of the cases the parents are separated and the mother is responsible for the family (62%). Most of the aggressors are male (78%). In the environment outside the family the aggressors are acquaintances or family friends (14%), inside the family environment the stepfather is identifi ed as the most frequent aggressor (18%). The data highlight characteristics which are similar to other studies, defi ning a certain pattern of this type of violence.